A new large squalodelphinid (Cetacea, Odontoceti) from Peru sheds light on the Early Miocene platanistoid disparity and ecology. Issue 4 (18th April 2018) - Bianucci, Giovanni; Bosio, Giulia; Malinverno, Elisa; de Muizon, Christian; Villa, Igor M.; Urbina, Mario; Lambert, Olivier
Abstract : The South Asian river dolphin ( Platanista gangetica ) is the only extant survivor of the large clade Platanistoidea, having a well-diversified fossil record from the Late Oligocene to the Middle Miocene. Based on a partial skeleton collected from the Chilcatay Formation (Chilcatay Fm; southern coast of Peru), we report here a new squalodelphinid genus and species, Macrosqualodelphis ukupachai . A volcanic ash layer, sampled near the fossil, yielded the 40 Ar/ 39 Ar age of 18.78 ± 0.08 Ma (Burdigalian, Early Miocene). The phylogenetic analysis places Macrosqualodelphis as the earliest branching squalodelphinid. Combined with several cranial and dental features, the large body size (estimated body length of 3.5 m) of this odontocete suggests that it consumed larger prey than the other members of its family. Together with Huaridelphis raimondii and Notocetus vanbenedeni, both also found in the Chilcatay Fm, this new squalodelphinid further demonstrates the peculiar local diversity of the family along the southeastern Pacific coast, possibly related to their partition into different dietary niches. At a wider geographical scale, the morphological and ecological diversity of squalodelphinids confirms the major role played by platanistoids during the Early Miocene radiation of crown odontocetes.